Beneath the surface in autoimmune hemolytic anemia: pathogenetic networks, therapeutic advancements and open questions - Costa, Alessandro; Mulas, Olga; Mereu, Angela Maria; Schintu, Mercede; Greco, Marianna; Caocci, Giovanni (Frontiers in Immunology, 2025)
In recent years, the pathophysiologic framework of autoimmune hemolytic anemias (AIHAs) has evolved considerably, extending beyond the simplistic paradigm of antibody-mediated red blood cell (RBC) destruction, which is now recognized as a downstream consequence of a broader immune dysregulation. AIHA is fundamentally orchestrated by a complex interplay between innate and adaptive immune components, including autoreactive B and T lymphocytes, macrophages, and the reticuloendothelial system. Central to disease pathogenesis are two interrelated mechanisms: clonal B-cell expansion with autoantibody production and complement activation. These immunologic processes support the heterogeneity of AIHA, delineating distinct clinical entities such as warm AIHA, cold agglutinin disease/syndrome (CAD/CAS), and atypical variants, each characterized by specific therapeutic susceptibilities. Glucocorticoids remain the standard first-line therapy for warm AIHA; in contrast, CAD/CAS is increasingly managed with agents targeting B-cell function or complement activation, including rituximab and sutimlimab. However, therapeutic algorithms are rapidly shifting, particularly in the context of treatment-refractory disease. Emerging therapeutics targeting the classical complement pathway include novel anti-C1s monoclonal antibodies such as riliprubart, which exhibits an extended half-life due to enhanced affinity for the neonatal Fc receptor. Parallel strategies aim to disrupt B-cell receptor (BCR) signaling cascades, employing Bruton tyrosine kinase (BTK) inhibitors such as ibrutinib, spleen tyrosine kinase (SYK) inhibitors such as fostamatinib and sovleplenib, and phosphoinositide 3-kinase (PI3K) inhibitors such as parsaclisib. Collectively, these advances are reshaping the therapeutic landscape of AIHA toward a precision medicine model guided by mechanistic insights into disease biology. In this review, we delineate the evolving immunopathogenesis of AIHAs and examine emerging therapeutic strategies, integrating their underlying rationale, clinical data, and implications for future treatment paradigms.